Chapter 10 Early radio in late colonial India Historiography, geography, audiences - Duggal, Vebhuti (Taylor & Francis, 2023)
As previous research on the role of the radio in (post)colonial India has shown, radio broadcasting is deeply implicated in the narratives of empire and postcolonial nation-building. Radio thus becomes seemingly synonymous with the imperial project during colonialism and with the national project in the postcolonial period. In this chapter, we shift scholarly attention to public discourse and audience formation during the early years of radio in colonial India (1925 and 1936). We analyse how early radio impacted people's perception of space and place by re-structuring the geographies of 'home', 'world', and 'empire'. We also show how the radio affected audiences along the rural-urban divide, re-configuring their understandings of sound, technology and listening.